Born Too Early and Too Small: Higher Order Cognitive Function and Brain at Risk at Ages 8–16 - Córcoles-Parada, Marta; Giménez-Mateo, Rocio; Serrano-del-Pueblo, Victor; López, Leidy; Pérez-Hernández, Elena; Mansilla, Francisco; Martínez, Andres; Onsurbe, Ignacio; San Roman, Paloma; Ubero-Martinez, Mar; Clayden, Jonathan D.; Clark, Chris A.; et al. (Frontiers in Psychology, 2019)
Prematurity presents a risk for higher order cognitive functions. Some of these deficits manifest later in development, when these functions are expected to mature. However, the causes and consequences of prematurity are still unclear. We conducted a longitudinal study to first identify clinical predictors of ultrasound brain abnormalities in 196 children born very preterm (VP; gestational age≤32 weeks) and with very low birth weight (VLBW; birth weight≤1500g). At ages 8-16, the subset of VP-VLBW children without neurological findings (124) were invited for a neuropsychological assessment and an MRI scan (41 accepted). Of these, 29 met a rigorous criterion for MRI quality and an age, and gender-matched control group (n=14) was included in this study. The key findings in the VP-VLBW neonates were: a) 37% of the VP-VLBW neonates had ultrasound brain abnormalities; b) gestational age and birth weight collectively with hospital course (i.e. days in hospital, neonatal intensive care, mechanical ventilation and with oxygen therapy, surgeries, and retinopathy of prematurity) predicted ultrasound brain abnormalities. At ages 8-16, VP-VLBW children showed: a) lower intelligent quotient (IQ) and executive function; b) decreased grey and white matter integrity; c) IQ correlated negatively with cortical thickness in higher order processing cortical areas. In conclusion, our data indicate that facets of executive function and IQ are the most affected in VP-VLBW children likely due to altered higher order cortical areas and underlying white matter.